BORDERLESS CONNECTIVITY: THE ROLE OF DIGITAL TECHNOLOGY IN CONNECTING THE GLOBAL ECONOMY - Loso Judijanto (CV. Adiba Aisha Amira, 2024)
Digital technology has become a major catalyst in connecting the global economy, enabling the flow of information, goods and services across geographical boundaries with unprecedented speed and efficiency. Through the internet and various digital platforms, companies of all sizes can reach international markets, stimulating economic growth and collaboration between countries. These technologies not only open up new opportunities for small and medium-sized businesses, but also strengthen a more integrated and dynamic economic network. However, the global adoption of digital technologies also presents complex challenges. Data security, unequal access to technology, and the need for cross-border regulation are critical issues that must be addressed to ensure the benefits of technology can be enjoyed equally. Cooperation between the government, private sector and society is essential in creating policies that encourage digital literacy and responsible use of technology. With a thoughtful approach, digital technology has great potential to continue advancing global connectivity and its contribution to the world economy.